(untitled) (Research, Society and Development, 2023)
Introduction: The premature newborn has an immaturity of the pulmonary system which leads him to a need for comprehensive care and care to avoid possible complications, the physical therapist works with a multidisciplinary team in the Neonatal Intensive Care Unit, using respiratory techniques with the objective of contributing to the recovery and prevention of neonates, aiming at independence and improvement of respiratory capacity, in order to reduce hospitalization time and increase quality of life. Objective: To analyze, based on the available scientific literature, the benefit of the Physiotherapist in the Neonatal Intensive Care Unit when using respiratory therapy techniques. Methodology: This is an integrative literature review with a search carried out in the following databases: VHL, PEDro, PubMed, Scielo in the period from 2012 to 2022. Results: 6 articles were captured that portray respiratory physiotherapy techniques for this purpose. analyze the benefit of respiratory therapy. Conclusion: The respiratory physiotherapist works with several techniques aimed at the recovery and prevention of the neonate; however, the managements may not be effective, cause pain and generate harm if applied incorrectly and by a non-specialized professional.